PERCEPÇÃO DOS PROFISSIONAIS DA EQUIPE ESTRATÉGIA SAÚDE DA FAMÍLIA SOBRE O PROGRAMA PREVINE BRASIL - SERRA, Raquel Borges (2024)
Introduction: Primary Health Care underwent profound change with the launch of the Previne Brasil Program in 2019, bringing changes to financing criteria with the introduction of new assistance assessment instruments to guarantee resources, through weighted capture criteria, which takes into account the number of users registered in the Unified Health System, payment for performance, which evaluates the achievement of pre-established indicators and the incentive for strategic health actions, such as the existence of Units with Health on the Time, Mobile Dental Unit, Dental Specialties Center and Regional Dental Prosthesis Laboratory. Objective: to analyze the perception of professionals from the Family Health Strategy team about the Previne Brasil Program. Methodology: This is a descriptive study, with a qualitative approach. Data were collected from January to July 2024, through semi-structured interviews, with professionals from eight Family Health Strategy teams, located in the Municipality of São Luís - MA and distributed between urban and rural areas of the Districts Health. The information obtained was analyzed using content analysis and the IRAMUTEQ® software. The research was approved by the Research Ethics Committee (CEP) of the University Hospital of the Federal University of Maranhão (HU/UFMA), and authorized through CAAE: 75695523.2.0000.5086, embodied opinion no. 6.650.169 and Municipal Health Secretariat of São Luís – MA through the letter of consent. Results: 32 professionals participated in the research, including 8 (25%) Nurses, 5 (15.65%) Nursing Technicians, 2 (6.25%) Dentists, 7 (21.87%) Doctors and 10 (31 .25%) Community Health Agents. All were women (100%), aged between 41 and 50 years (34.7%) and had worked in the ESF between one and more than ten years. Two categories of the Descending Hierarchical Classification (CHD) emerged, subcorpus A and B and were called new financing of Primary Care and Perception of professionals. Final considerations: The research allowed analyzing the perception of professionals from the Family Health Strategy team about the Previne Brasil Program, and raising reflections on the impacts that the new financing model brought to the routines and work processes of eSF teams, which could identify the strategies implemented and the difficulties faced.